CHALLENGES FACED BY STUDENTS IN STUDYING TARKÎB WITH ZOOM PLATFORM DURING PANDEMIC - Siti Muflichah; Ridha Darmawaty; Puji Sri Rahayu (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2021)
This paper discusses the difficulties of Arabic department students when dealing with Tarkîb al-Marfû’ât subject and the using of Zoom/forced technology due to the Covid-19 pandemic. Using the qualitative approach, this paper aimed to explore whether students were negatively impacted by switch of learning mode to online. Interviews were conducted to nine students who live in remote areas, and it revealed that those students experienced delay in learning the subject due to their lack of the internet availability. Teaching activities were not optimal due to signal interference so that the exposure to the relevant material was not comprehensive. Moreover the students also lacked understanding to the subject because of the specific difficulty level of the subject. The students missed additional explanations and material from the lecturer, even equipped examples. This paper contributes to educational policies in the ways Indonesian government addresses distance learning for students in Islamic higher education.